Peer support in early intervention in psychosis: a qualitative research study. (4th March 2022) - Nguyen, Jen; Goldsmith, Lucy; Rains, Luke Sheridan; Gillard, Steve
Abstract: Background: There is evidence that peer support can be helpful for people suffering from psychosis, but there is a lack of research describing peer support in the context of Early Intervention in Psychosis (EIP). Aims: We aim to investigate the key elements of peer support in EIP and how peer support workers might best be recruited and supported in their work. Method: We used purposive sampling to recruit seven participants for semi-structured interviews. Thematic analysis was used to analyse the data. Results: Destigmatisation of psychotic experiences is a central concept that runs through all themes. Participants perceived peer support as a meaningful source of support that could provide benefits to peers (service users) and peer support workers. Themes included a "symbol of hope, " "practical support, " "mutuality and reciprocity, " "bridge between service and peers, " "ideal requirements of peer support workers, " "delivering peer support, " and "team-working and role clarification." Conclusions: Peer support makes a strong contribution to destigmatising psychosis. Findings potentially contribute to developing peer support workers' roles in EIP. Future research is recommended to investigate the perspectives of ethnic minorities on this topic and practical applications of these findings.